Roundtable discussion: how the World Hepatitis Summit 2015 strengthened stakeholders' efforts to combat viral hepatitis. Issue 1 (December 2016) - Gore, Charles; Wiktor, Stefan; Goldberg, David; Hutchinson, Sharon; Oñate Moreno, Jose; Peck, Raquel
Abstract The inaugural World Hepatitis Summit was jointly convened by the World Health Organization (WHO) and the World Hepatitis Alliance and hosted by the Scottish Government and supported by Glasgow Caledonian University and Health Protection Scotland in September 2015. The three day event convened a broad range of stakeholders to meet and share ideas, experience and best practice in addressing the many facets of viral hepatitis prevention, diagnosis and treatment. With the next World Hepatitis Summit scheduled to take place from 1 to 3 November 2017, the World Hepatitis Alliance askedHepatology, Medicine and Policy to commission a roundtable discussion article in order to encourage reflection on how the 2015 Summit was significant for stakeholders' efforts and why it is important to keep the momentum going ahead of the World Hepatitis Summit 2017 and in the light of the newly adopted first-ever Global Health Sector Strategy on Viral Hepatitis.